WOMEN, WAGES AND DISCRIMINATION: SOME EVIDENCE INDONESIA - SRI SUSILOWATI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2005)
The study has illustrated that gender earnings differential exists in Indonesian labor market. Among the sector of employment, the highest male female earnings differential was reported in agriculture sector and the lowest in formal job status. The differentials suggest that males receive an earnings premium in the form of constant mark up, which dominates all other factors contributing to wage discrimination. By using Oaxaca (1973) decomposition method we found that male – female earnings differentials that exist in Indonesian labor market is attributable to labor market discrimination rather than differences in endownment characteristics among workers. The study has demonstrated that education is one of the main determinants for the differentials between genders.